Supercritical fluid technology for gastroretentive formulations - Ahmed, Elizabeth Hannah (2013)
The oral route for drug administration offers an efficient and convenient method for drug delivery. However, there is an assortment of drugs which exhibit narrow absorption windows in the upper small intestine and as a result demonstrate limited bioavailabilities. One approach in the improvement of bioavailability in these cases is to retain the delivery system proximal to the absorption window for a prolonged period of time. Although controlled release products are widely available on the market, marketed gastroretentive systems remain elusive. This work explores the manufacture and characterisation of a multi-unit gastroretentive system utilising the biocompatible polymer poly (lactic-coglycolic acid). The novel PGSS technique enables the production of PLGA particles whilst omitting the use of volatile organic solvents. Morphological and microCT analyses of the particles revealed a highly porous matrix with porosity values in the order of 30-40%. The relationship between porosity, density and in vitro floating ability for particles with sizes between 100-2000 J.1m revealed that particle size plays an important role; larger microparticles possess decreased density, higher porosity and increased buoyancy. Encapsulation of two model drugs, riboflavin and furosemide, was carried out during the processing step with high encapsulation efficiencies (80-100%) being revealed. Release of the drugs in PBS (pH7.4) was found to be sustained over a period of 24 hours with a decrease in cumulative release in simulated gastric fluid (pHl.2). The introduction of the hydrophilic polymer poly(ethylene glycol) was found to modulate release rate; PEG with a molecular weight equal of more than 3 KDa increased the rate of release in PBS media up to 20% over hrs, however this was not observed for release in SGF. A comparison of morphology prior to and following exposure to the release media confirms that the emergence of intricate porous channels on exposure to the release medium is related to an increase in release rate. In order to augment the gastroretentive potential of the system the mucoadhesive polymer, chitosan was incorporated both as a post processing surface modification and as part of the initial formulation. ToF-SIMS surface analysis confirmed the presence of chitosan at the surface of the particles in both cases. Initially the potential for the particles to interact with mucus was evaluated utilising in vitro tests. The presence of chitosan significantly improved adsorption of mucin to particles, as well as enhancing adhesion of particles to a mucus producing epithelial cell layer. The thiolated chitosan derivative chitosan-N-acetyl-cysteine demonstrated an increase in adhesion of mucin solution; however the modified chitosan resulted in a decrease in adhesion to mucus producing cell line which was considered to be a result of the mucolytic actions it may exert on the mucus layer. Oral administration of buoyant particles to a rat model improved the pharmacokinetics of the anti-hypoglycaemia drug metformin, with addition of mucoadhesive properties providing further improvement. This study demonstrates that introduction of buoyancy and mucoadhesion functionalities to particles prepared by the PGSS method could improve delivery of drugs demonstrating narrow absorption windows in the upper small intestine.